Sensory Function and Chronic Pain in Multiple Sclerosis - Rogier J. Scherder; Neeltje Kant; Evelien T. Wolf; Bas C. M. Pijnenburg; Erik J. A. Scherder (Pain Research and Management)
Objective. To examine whether hypoesthesia and chronic pain are related in patients with MS. Methods. Sixty-seven MS patients with pain and 80 persons without MS were included. Sensory functioning was tested by bedside neurological examination. Touch, joint position (dorsal column-medial lemniscus pathway), temperature sense, and pain (spinothalamic tract) were tested. Pain intensity was measured by the Colored Analogue Scale (CAS Intensity) and the Faces Pain Scale (FPS); pain affect was also measured by CAS Affect and Number of Words Chosen-Affective (NWC-A). Mood was assessed with the SCL-90 anxiety and depression subscales and the Beck Depression Inventory (BDI). Results. A significant negative relationship was found between pain intensity and the function of the dorsal column-medial lemniscal pathway, but not with the spinothalamic tract. Conclusion. In addition to the already known relation between hyperesthesia and pain, hypoesthesia for touch and joint position also seems to be related to chronic pain in MS patients.